A Study of Determinants of Hotel Prices in Lagos, Nigeria - Yakubu, G. A.; Yakubu, A. O. (European Journal of Applied Sciences, 2022)
The research study is aimed at determining the Hotel prices in Lagos metropolis. Attributes of the location, chain firms, years of operations, numbers of rooms, and numbers of house-keepers influence room rates in hotels. A regression model was developed for various hotel segments in Lagos state. Regression model provides a more flexible and complete characterization of the determinants of the hotel prices at the higher and lower tail of the distribution. Data was obtained using structured questionnaires through non-probability sampling in Victoria Island, Ikoyi and Lekki Pennisula were various hotels are located. The 30 questionnaire recovered was analyzed using SPSS and interpreted using descriptive statistic The findings reveal that, franchise, resort location of hotels and year of establishment are significant attributes that determines hotel average room rate in Lagos, Nigeria.